PENGARUH KUALITAS AUDIT TERHADAP LOYALITAS KLIEN DENGAN MEDIATOR KEPUASAN KLIEN - Ria Nathasia, 10.05.52.0131; Dwi Nugroho, Arief Himmawan (Students Journal of Accounting and Banking, 2014)
The purpose of this study was to prove the hypothesis proposed and analyzed. The hypothesis is made concerning the effect of audit quality on client loyalty client satisfaction with the mediator. This research method uses object and obtained 38 BPR in Semarang, Tegal and Ungaran. Purposive sampling method used in data collection and analyzes were performed using SPSS 16. Responsiveness of audit quality dimensions and experiences have a direct impact on client loyalty. The results of this study, the dimensions of quality audits of responsiveness and experience have an influence on client loyalty. However, audit quality has no effect on client satisfaction.Keywords: Audit Quality, Client Satisfaction, Client Loyalty